Molecular Mechanism of Stimulation of Na-K-ATPase by Leukotriene D4 in Intestinal Epithelial Cells - Nepal, Niraj (Int J Mol Sci, 2021)
Na-K-ATPase provides a favorable transcellular Na gradient required for the functioning of Na-dependent nutrient transporters in intestinal epithelial cells. The primary metabolite for enterocytes is glutamine, which is absorbed via Na-glutamine co-transporter (SN2; SLC38A5) in intestinal crypt cells. SN2 activity is stimulated during chronic intestinal inflammation, at least in part, secondarily to the stimulation of Na-K-ATPase activity. Leukotriene D4 (LTD4) is known to be elevated in the mucosa during chronic enteritis, but the way in which it may regulate Na-K-ATPase is not known. In an in vitro model of rat intestinal epithelial cells (IEC-18), Na-K-ATPase activity was significantly stimulated by LTD4. As LTD4 mediates its action via Ca-dependent protein kinase C (PKC), Ca levels were measured and were found to be increased. Phorbol 12-myristate 13-acetate (PMA), an activator of PKC, also mediated stimulation of Na-K-ATPase like LTD4, while BAPTA-AM (Ca chelator) and calphostin-C (Cal-C; PKC inhibitor) prevented the stimulation of Na-K-ATPase activity. LTD4 caused a significant increase in mRNA and plasma membrane protein expression of Na-K-ATPase α1 and β1 subunits, which was prevented by calphostin-C. These data demonstrate that LTD4 stimulates Na-K-ATPase in intestinal crypt cells secondarily to the transcriptional increase of Na-K-ATPase α1 and β1 subunits, mediated via the Ca-activated PKC pathway.